2002
DOI: 10.1007/bf03017903
|View full text |Cite
|
Sign up to set email alerts
|

In children, nitrous oxide decreases pain on injection of propofol mixed with lidocaine

Abstract: P Pu ur rp po os se e: : To investigate if 50% nitrous oxide reduces the pain during injection of propofol mixed with lidocaine in children.M Me et th ho od ds s: : Healthy children undergoing iv induction of general anesthesia for elective surgery were recruited into this prospective, randomized, double-blind study. None of the patients received any premedication except for eutectic mixture of local anesthetics cream. Before induction of anesthesia with propofol 1% mixed with lidocaine 0.05% (propofol dose 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Physical and pharmacological approaches have been proposed to reduce propofol injection pain. These attempts include pretreatment or premixture of propofol with lidocaine [4,9], ketamine [3,4], thiopental sodium [10], N 2 O [11], opioid [12] , cooling [13], diluting the propofol solution [14], or changing the propofol formulation [15]. However, none of these strategies is very effective in eliminating the pain completely.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and pharmacological approaches have been proposed to reduce propofol injection pain. These attempts include pretreatment or premixture of propofol with lidocaine [4,9], ketamine [3,4], thiopental sodium [10], N 2 O [11], opioid [12] , cooling [13], diluting the propofol solution [14], or changing the propofol formulation [15]. However, none of these strategies is very effective in eliminating the pain completely.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of pain was 4% after nitrous oxide and 36% in control group. [32] f) Lignocaine pre-treatment-This has local anesthetic effect on vein wall. Mc Culloch et al suggested the use of 10mg lignocaine 20 seconds prior to propofol.…”
Section: Discussion 21 Different Formulations Of Propofol Derived Fomentioning
confidence: 99%
“…Recommendation: The administration of nitrous oxide, alone or in combination with EMLA is associated with effective sedation and pain relief in children receiving injections [59][60][61] (A).…”
Section: (A)mentioning
confidence: 99%